A self-healable fluorescence active hydrogel based on ionic block copolymers prepared via ring opening polymerization and xanthate mediated RAFT polymerization. Issue 10 (21st February 2018) - Banerjee, Sovan Lal; Hoskins, Richard; Swift, Thomas; Rimmer, Stephen; Singha, Nikhil K.
Abstract : In this work we report a facile method to prepare a fluorescence active self-healable hydrogel via the incorporation of fluorescence responsive ionic block copolymers (BCPs). Abstract : In this work we report a facile method to prepare a fluorescence active self-healable hydrogel via incorporation of fluorescence responsive ionic block copolymers (BCPs). Ionic block copolymers were prepared via a combined effect of ring opening polymerization (ROP) of ε-caprolactone and xanthate mediated reversible addition–fragmentation chain transfer (RAFT) polymerization. Here polycaprolactone (PCL) was modified with xanthate to prepare a PCL based macro-RAFT agent and then it was utilized to prepare block copolymers with cationic poly(2-(methacryloyloxy)ethyltrimethyl ammonium chloride) (PCL- b -PMTAC) and anionic poly(sodium 4-vinylbenzenesulfonate) (PCL- b -PSS). During the block formation, the cationic segments were randomly copolymerized with a trace amount of fluorescein O -acrylate (FA) (acceptor) whereas the anionic segments were randomly copolymerized with a trace amount of 9-anthryl methylmethacrylate (AMMA) (donor) to make both the segments fluorescent. The block copolymers form micelles in a DMF : water mixture (1 : 4 volume ratio). The ionic interaction of two BCPs was monitored via Förster resonance energy transfer (FRET) and zeta potential measurements. The oppositely charged BCPs were incorporated into a polyacrylamide (PAAm) based hydrogel that demonstrated self-healing behavior and is also highly fluorescent.